2012
DOI: 10.1016/j.neuroscience.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal tissue of patients with refractory temporal lobe epilepsy is associated with astrocyte activation, inflammation, and altered expression of channels and receptors

Abstract: Temporal lobe epilepsy (TLE) is the most common form of focal epilepsy. Previous research has demonstrated several trends in human tissue that, undoubtedly, contribute to the development and progression of TLE. In this study we examined resected human hippocampus tissue for a variety of changes including gliosis that may contribute to the development and presentation of TLE. The study subjects consisted of 6 TLE patients and 3 sudden-death controls. Clinicopathological characteristics were evaluated by H&E sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(151 citation statements)
references
References 36 publications
6
137
2
Order By: Relevance
“…It has been previously reported that changes in transcription and protein expression of GFAP can affect the morphology of astrocytes in brain (Morgan et al, 1997). In present study, the animals showed astrocyte activation after repeated PTZ administration as shown by the animal models of epilepsy (Bechstein et al, 2012;Das et al, 2012). Astrocyte undergoes various functional changes including proliferation (i.e.…”
Section: Evidence Suggests Neuroinflammation Is a Ubiquitous Pathologsupporting
confidence: 59%
“…It has been previously reported that changes in transcription and protein expression of GFAP can affect the morphology of astrocytes in brain (Morgan et al, 1997). In present study, the animals showed astrocyte activation after repeated PTZ administration as shown by the animal models of epilepsy (Bechstein et al, 2012;Das et al, 2012). Astrocyte undergoes various functional changes including proliferation (i.e.…”
Section: Evidence Suggests Neuroinflammation Is a Ubiquitous Pathologsupporting
confidence: 59%
“…medial amygdaloid nucleus and basomedial amygdaloid nucleus) (18) ( Table 1). In addition, recent clinical studies showed that Kir4.1 expression was significantly diminished in patients with temporal lobe epilepsy (20)(21)(22). All these results suggest that the reduced activity of astrocytic Kir4.1 channels evokes GTC and/or temporal lobe seizures, probably by disrupting spatial K + buffering, which consequently elevates extracellular K + and glutamate concentrations.…”
Section: Discussionmentioning
confidence: 82%
“…All of the mutations in patients with EAST syndrome cause drastic decreases in K + buffering currents mediated by both Kir4.1 and Kir4.1/5.1 channels, implying that the impaired functioning of Kir4.1 disrupts spatial K + buffering and causes epileptic seizures (15)(16)(17). In addition, it has also been shown that expressional levels of Kir4.1 were altered in animal models of epilepsy (18,19), as well as in patients with temporal lobe epilepsy (20)(21)(22). All these findings strongly suggest that Kir4.1 channels are involved in the pathogenesis of GTC and/or temporal lobe seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that TGFb1 involved in neuronal excitability and/or glial scar formation in epilepsy via inflammatory process [6,15]. We hypothesize that altered TGFb1 may participate in inflammatory event, thus leading to seizure-induced neuronal damage in the brain; recurrent seizures eventually contribute to intractable epilepsy.…”
Section: Introductionmentioning
confidence: 84%